Early COVID-19 XBB.1.5 Vaccine Effectiveness Against Hospitalisation Among Adults Targeted for Vaccination, VEBIS Hospital Network, Europe, October 2023-January 2024 - Antunes, Liliana; Mazagatos, Clara; Martínez-Baz, Iván; Naesens, Reinout; Borg, Maria-Louise; Petrović, Goranka; Fatukasi, Terra; Jancoriene, Ligita; Machado, Ausenda; Oroszi, Beatrix; Husa, Petr; Lazar, Mihaela; et al. (Influenza and other respiratory viruses, 2024)
We conducted a multicentre test-negative case-control study covering the period from October 2023 to January 2024 among adult patients aged ≥ 18 years hospitalised with severe acute respiratory infection in Europe. We provide early estimates of the effectiveness of the newly adapted XBB.1.5 COVID-19 vaccines against PCR-confirmed SARS-CoV-2 hospitalisation. Vaccine effectiveness was 49% overall, ranging between 69% at 14-29 days and 40% at 60-105 days post vaccination. The adapted XBB.1.5 COVID-19 vaccines conferred protection against COVID-19 hospitalisation in the first 3.5 months post vaccination, with VE > 70% in older adults (≥ 65 years) up to 1 month post vaccination.
Keywords: vakcinace; účinnost vakcíny; Humans; Case-Control Studies; lidé středního věku; SARS‐CoV‐2 hospitalisation; studie případů a kontrol; Vaccination; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Europe; hospitalizace; vaccine effectiveness; COVID-19 Vaccines; Adult; COVID-19; ženské pohlaví; vakcíny proti COVID-19; Hospitalization; Male; Middle Aged; Adolescent; COVID‐19 XBB.1.5 vaccine; Aged, 80 and over; Young Adult; senioři nad 80 let; mužské pohlaví; SARS-CoV-2; Evropa; Vaccine Efficacy; mladiství